Effect of the addition of glycerol on hydrogen production from industrial municipal solid waste. (15th September 2016) - Zahedi, S.; Solera, R.; García-Morales, J.L.; Sales, D.
Abstract: The purpose of this study was to investigate the effect of glycerol supplementation (1% v/v) on the hydrogen production (HP) steps in thermophilic-dry dark fermentation of industrial municipal solid waste (IMSW) in batch mode. For this purpose, physicochemical and microbiological parameters were considered. The rates of HP and specific hydrogen production (SHP) almost doubled when adding 1% v/v crude glycerol to the IMSW. This result was in keeping with the high values of hydrolysis yield (75 ± 4%) and microbial activity (7.3 ∗ 10 −12 ± 0.9 ∗ 10 −12 l H2 /cell). Microbiological studies showed that the percentages of Eubacteria decreased slightly after the dark fermentation process. Archaea contents were not significant and the biogas produced was methane-free.